Factors Influencing Students’ Vocabulary Acquisition in English Language Learning - Suharvina; Nurdin Noni; Geminastiti Sakkir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to analyze students' vocabulary mastery levels and the internal and external factors that influence their vocabulary mastery in English learning at SMP Negeri 48 Makassar. This study used a mixed-methods approach, combining quantitative and qualitative data. Quantitative data were obtained through vocabulary tests consisting of multiple-choice and essay questions, while qualitative data were obtained through observation and interviews. The study sample was 30 grade VII-8 students selected using a purposive sampling technique.The results showed that students' vocabulary mastery levels were still relatively low, with an average score of 43.53 and a standard deviation of 17.92, indicating significant variation in ability among students. Qualitative findings revealed that internal factors such as motivation, self-confidence, cognitive ability, and memory influence students' vocabulary acquisition. Furthermore, external factors such as the school environment, teacher teaching methods, peer group environment, and family support also play a significant role in the vocabulary learning process. Observations indicate that the learning process is still dominated by conventional methods with limited use of learning media, resulting in students experiencing difficulties in actively using vocabulary in communication.Thus, it can be concluded that students' vocabulary acquisition is influenced by a combination of internal and external factors. Therefore, more interactive and contextual learning strategies and optimal learning environment support are needed to improve students' vocabulary acquisition.